You are a bad ass how to stop doubting your greatness and start living an awesome life - Sincero, Jen 1965- (Philadelphia Running Press, 2013)
You are a badass is the self-help book for people who desperately want to improve their lives but don't want to get busted doing it. In this refreshingly entertaining how-to guide, best selling author and world-traveling success coach, Jen Sincero, serves up 27 bite-sized chapters full of hilariously inspiring stories, sage advice, easy exercises, and the occasional swear word, helping you to: identify and change the self-sabotaging beliefs and behaviors that stop you from getting what you want; create a life you totally love. And create it now.; make some damn money already. The kind you've never made before
Chapter 1: My subconscious made me do -- Chapter 2: The g-word -- Chapter 3: Present as a pigeon -- Chapter 4: The big snooze -- Chapter 5: Self-perception is a zoo -- Chapter 6: Love the one you is -- Chapter 7: I know you are but what am I? -- Chapter 8: What are you doing here? -- Chapter 9: Loincloth man -- Chapter 10: Meditation 101 -- Chapter 11: Your brain is your bitch -- Chapter 12: Lead with your crotch -- Chapter 13: Give and let give -- Chapter 14: Gratitude: the gateway drug to awesomeness -- Chapter 15: Forgive or fester -- Chapter 16: Loosen your bone, Wilma -- Chapter 17: It's so easy once you figure out it isn't hard -- Chapter 18: Procrastination, perfection, and a polish beer garden -- Chapter 19: The drama of overwhelm -- Chapter 20: Fear is for suckers -- Chapter 21: Millions of mirrors -- Chapter 22: The sweet life -- Chapter 23: The almighty decision -- Chapter 24: Money, your new best friend -- Chapter 25: Remember to surrender -- Chapter 26: Doing vs. spewing -- Chapter 27: Beam me up, Scotty
Keywords: Self-actualization (Psychology); Self-help techniques